Design, manufacturing and applications of auxetic tubular structures: A review. (June 2021) - Luo, Chen; Han, Chuan Zhen; Zhang, Xiang Yu; Zhang, Xue Gang; Ren, Xin; Xie, Yi Min
Abstract: Auxetic materials and structures have attracted increasing attention because of their extraordinary mechanical properties. Various types of auxetic tubular structures have been designed and studied in diverse fields, including mechanical and medical engineering. In this paper, design methods and advanced manufacturing technologies of auxetic tubular structures are extensively reviewed, including various types of cellular auxetic tubes, nonporous and porous auxetic tubes, macro and micro auxetic tubes. Furthermore, auxetic behaviour, mechanical properties and potential applications of auxetic tubular structures are elaborated. Finally, the challenges and opportunities on the auxetic tubes are discussed to inspire future research work. Highlights: Design methods and advanced manufacturing technologies of auxetic tubular structures are extensively reviewed for the first time. Auxetic behaviour, mechanical properties and potential applications of auxetic tubular structures are introduced. Challenges and opportunities on the auxetic tubes are discussed to inspire future work.